Interpretation of bronchograms and chest radiographs in patients with chronic sputum production. Issue 4 (April 1987) - Currie, D C; Cooke, J C; Morgan, A D; Kerr, I H; Delany, D; Strickland, B; Cole, P J
Abstract : Bronchograms and plain chest radiographs of 27 patients with chronic sputum production were reported separately in random order and independently by two pulmonary radiologists to establish the diagnostic rate of each investigation and to assess interobserver variation. Both radiologists agreed on the presence of bronchiectasis on bronchography in 19 of 27 (70%) patients and in 94 of 448 (21%) bronchopulmonary segments. One radiologist only interpreted the films as showing bronchiectasis in a further two (7%) patients and 26 (6%) segments. There was more disagreement about the presence or absence of individual bronchographic abnormalities. Two main groups of patients with bronchiectasis were identified by bronchography: 11 with bronchiectasis alone and eight with bronchiectasis and bronchographic features suggestive of "chronic bronchitis". There was no clinical difference between these two groups. Plain chest radiographs were insensitive, being diagnostic (both radiologists agreeing) of bronchiectasis in only nine of 19 (47%) patients with definite bronchiectasis on bronchography.